2012
DOI: 10.5539/ijc.v4n5p9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Models of the Prebiotic Replication of dsRNA under Thermal Cycling Conditions

Abstract: We present computational models for the replication of double stranded RNA (dsRNA) or related macromolecules under thermal cycling conditions that would reflect prebiotic (i.e. non-enzymatic) environments. Two models of the replication of dsRNA are represented as multi-step chemical systems. The objective of this investigation was to better understand the kinetic features of such chemical systems. It is shown that thermal cycling in a chemical system is advantageous (relative to a fixed temperature) if there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Like systems biology and systems engineering, a critical feature of systems chemistry is that unexpected outcomes may arise which may not be predicted from examining the behavior of the individual components of the system. We have studied, both computationally and analytically, several simple chemical systems and have found that complex behavior can arise over time from even simple systems [41][42][43]. Recently we and others have focused on chemical systems to understand the generation of homochirality in prebiotic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Like systems biology and systems engineering, a critical feature of systems chemistry is that unexpected outcomes may arise which may not be predicted from examining the behavior of the individual components of the system. We have studied, both computationally and analytically, several simple chemical systems and have found that complex behavior can arise over time from even simple systems [41][42][43]. Recently we and others have focused on chemical systems to understand the generation of homochirality in prebiotic environments.…”
Section: Discussionmentioning
confidence: 99%